Acute Retinal Necrosis: Clinical Features, Diagnostic Pitfalls, Treatment, and Outcome of an Insidious Disease in Children. Case Report and Review of the Literature - Mapelli, Chiara; Milella, Paolo; Donà, Caterina; Nassisi, Marco; Osnaghi, Silvia; Viola, Francesco; Agostoni, Carlo; Minoia, Francesca; Filocamo, Giovanni (Frontiers in Pediatrics, 2022)
Objective: to explore clinical features, diagnostic work-up, treatment and outcomes of pediatric patients with acute retinal necrosis (ARN), to propose a standardized management of this condition in childhood. Methods: clinical manifestations, diagnostic work-up and treatment of three pediatric cases with ARN were analyzed. Furthermore, a review of the literature was performed from January 1990 to November 2021, focused on: 1) clinical presentation; 2) differential diagnosis, including both infectious and non-infectious conditions; 3) key role of diagnostic techniques; 4) currently available treatments. Results: data from 72 children with ARN (69 from literature and 3 from our center) were analyzed. The most frequent presenting symptoms were red eye resistant to topical treatment (57%) and altered vision (58%), 25 patients had bilateral involvement. In 30% a known history of herpetic infection was reported. PCR testing on anterior chamber and/or vitreous sampling was performed in 46 cases (64%) and was diagnostic in 88% of them, with Herpes Simplex virus (HSV) 2 being the most frequently identified pathogen (57%). All patients underwent systemic antiviral therapy (16% only oral); adjuctive intravitreal injections were performed in the 21% of them. Conclusions: ARN is a rare but severe ocular infection presenting as a panuveitis with occlusive retinal vasculitis and peripheral retinal necrosis. Varicella-Zoster virus (VZV) and HSV 1-2 are most frequently implicated. Due to a high incidence of rhegmatogenous retinal detachment and optic atrophy, ARN has a poor prognosis with a potentially severe impact on visual function. Although a prompt recognition is crucial to prevent complications, ARN diagnosis in children is still challenging.